Callus induction and plant regeneration from mature embryos of some Syrian durum wheat Triticum durum Desf.. varieties (Journal of Hama University, 2021)
This work was conducted in the laboratory of plant biotechnology affiliated to the National Commission of Biotechnology (NCBT) - Ministry of Higher Education, in order to produce callus from the mature embryos of four Syrian durum wheat varieties and plant regeneration from this callus. The results indicate that the significantly highest percentage of callus induction was inBouhoth.11 (76.11), while the lowest was in Bohooth.7 (54.16%). The rate of embryonic callus formation was significantly the highest with the application of 2 mg of 2,4-D in Doma.1, Bouhoth.7, Bouhoth.11 and Cham.3 varieties (73.33, 70, 68.57 and 66.66%, respectively). The plant regeneration rate was significantly the highest with the application of 1 mg.l-1of BAP and 0.1 mg.l-1 of IAA (47.50%). The shoots formation rate was significantly the highest with the application of 1 mg.l-1of BAP and 0.1 mg.l-1 of IAA (11.21%).There were no significant differences between the varieties in terms of the number of formed shoots. Results indicate that the percentage of the callus induction is determined by the concentration of 2,4-D in the induction media. It is very essential to add balanced amounts of both auxin and cytokinin, but the cytokinin to auxin ratio should be more than one to improve the regeneration percentage and the number of formed shoots.